Penile Siliconoma: A Case Report - Ifran, Ifran (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2024)
Introduction. The use of liquid silicone, paraffin and other types of mineral oil with the aim of increasing the size and changing the contours of the penis is well known in primitive communities. Despite the many serious complications resulting from this practice. Cases of penile siliconoma have been widely reported.Case. A 66-year-old man comes to the Primary Health Center with complaints of swelling, accompanied by purulent wounds, pain, and shortening of the penis. The patient had injected silicone (Rita hair oil) in his penis by injecting the shaft of his penis, he began to wear silicone about ± 2 years ago. On genital exam found swelling and purulent wounds on the penis, contours irregular penis, flat surface and not bumpy, tenderness (+), with a soft consistency; laboratory examination showed leukocytosis (21 x 103/µL).Discussion. Siliconoma penis occurs due to continuous irritation over a long period of time with silicone. Rejection reaction to a foreign body as a normal response of the body appears in the form of inflammation, causing clinical symptoms such as pain, swelling of the penis, induration, ulceration, edema, scarring, discoloration of the skin on the penis, deformity, pain during erection and inability to perform sexual activities.Conclusion. Siliconoma of the penis occurs as a result of the injection of a liquid with a high viscosity in this case silicone with the aim of enlarging the penis has many consequences damaging the sexual and cosmetic functions of the organ.